PENGARUH PERMINTAAN TERHADAP OUTCOME SEKOLAH MENENGAH ATAS DI KOTA SURABAYA - Soejoto, Ady; Rachmawati, Lucky; Dewi, Retno Mustika (UNIVERSITAS NEGERI SURABAYA, 2014)
This research aim to determine the effect of demand on high school outcomes. The results showed the economic, demographic, educational and social environment have a significant effect on the academics ability. Partially no positive influence of economic factors and academic ability but the effect is not significant, a significant positive influence factor is education of parents. The higher the parents 'education level the higher the students' academic abilities. further more significant negative influence of demographic, social environment while having no effect on students' academic abilities. Another finding no direct effect on the economic demographics, but no effect indirectly on academic ability